Pengaruh Fleksibilitas Jam Kerja, Stress Kerja Dan Motivasi Kerja Terhadap Produktivitas Karyawan (Studi Pada Karyawan Kembang Jaya Wedding Service Klaten) - Pambudi, Dani Surya (Journal of Indonesian Economic Research, 2024)
This research aims to analyze the influence of Flexibility of Working Hours, Work Stress, Work Motivation on Employee Productivity in the Study of Kembang Jaya Wedding Service Klaten Employees. The population in this study were all employees of Kembang Jaya Wedding Service Klaten. The sample for this research was 50 respondents, with the sampling technique used, namely saturated sampling. This research used a quantitative approach, and was processed using IBM SPSS Version 29.0. The data collection method uses a questionnaire method, while the data analysis technique uses multiple regression analysis which is supported by the t test and f test as well as classical assumptions consisting of the normality test, multicollinearity test and heteroscedasticity test. The results of the research show that Flexibility of Working Hours has a positive and significant influence on Employee Work Productivity, Job Stress has a negative and significant influence on Employee Work Productivity, Work Motivation has a positive and insignificant influence on Employee Work Productivity, Flexibility of Working Hours, Job Stress, Work Motivation in general simultaneously has a positive and significant effect on employee productivity.